2012
DOI: 10.1111/j.1526-4610.2012.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Topiramate During Pregnancy and Risk of Birth Defects

Abstract: This retrospective study quantified the association between topiramate exposure during pregnancy and the risk of oral cleft or major congenital malformations, and suggested little or no increase in risk in comparison with exposure to other anti-epileptic drugs or to disease states, such as migraine, epilepsy, or diabetes. However, small numbers of events limit the strength of inferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Among 108 infants exposed to topiramate, five were malformed (OR = 1.44, 95% CI 0.58–3.58) [41] and another study found 15 malformed infants among 359 exposed with an RR of 2.2 (1.2–4.0) and noticed an increased risk for cleft lip [35]. The total malformation rate after topiramate exposure in monotherapy was 4.33% against 3.77% in unexposed infants but no specific effect on orofacial clefts was seen [51]. In retrospectively collected data an OR of 5.4 (95% CI 1.5–20.1) for cleft lip/palate was found after topiramate exposure [52].…”
Section: Resultsmentioning
confidence: 99%
“…Among 108 infants exposed to topiramate, five were malformed (OR = 1.44, 95% CI 0.58–3.58) [41] and another study found 15 malformed infants among 359 exposed with an RR of 2.2 (1.2–4.0) and noticed an increased risk for cleft lip [35]. The total malformation rate after topiramate exposure in monotherapy was 4.33% against 3.77% in unexposed infants but no specific effect on orofacial clefts was seen [51]. In retrospectively collected data an OR of 5.4 (95% CI 1.5–20.1) for cleft lip/palate was found after topiramate exposure [52].…”
Section: Resultsmentioning
confidence: 99%
“…Although the available evidence for an association between intrauterine TPM exposure and hypospadias is based on relatively small numbers of instances and needs to be confirmed in larger studies before it can be regarded as persuasive, it does raise concerns about the possible use of the drug during pregnancy, particularly when it is becoming more widely employed as a migraine preventative. In relation to migraine, Green et al (21) went into the matter of the risk of oral clefts and other major congenital malformations and concluded that TPM was no worse than other AEDs in these regards. The data of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Teratogenicity data derived from epidemiologic studies and claims data in women using immediate-release topiramate for approved migraine and epilepsy indications showed an increased risk of cleft lip with or without cleft palate in infants exposed to topiramate during the first trimester of pregnancy [31]. However, a subsequent retrospective analysis that quantified the association between topiramate exposure during pregnancy and the risk of oral cleft or major congenital malformations found little or no increase in risk when compared with exposure to other anti-epileptic drugs [31].…”
Section: Regulatory Affairsmentioning
confidence: 99%
“…However, a subsequent retrospective analysis that quantified the association between topiramate exposure during pregnancy and the risk of oral cleft or major congenital malformations found little or no increase in risk when compared with exposure to other anti-epileptic drugs [31]. The FDA approval of phentermine/topiramate ER in July 2012 included a risk evaluation and mitigation strategy (REMS) to inform patients and providers about teratogenic risk and the need to avoid fetal exposure [9].…”
Section: Regulatory Affairsmentioning
confidence: 99%